Bioactive Compounds, Their Mechanisms of Action, and Cardioprotective Effects of Pomegranate (Punica granatum): A Comprehensive Review - Esha Saeed; Farah Javed; Zoya Rana; Rashida Perveen; Iftikhar Younis Mallhi; Izza Amjad; Quratulain Maqsood; Nauman Ali Chaudhary; Saleha Binte Tahir; Arooj Fatima; Noor Fatima Rasheed; Esther Ugo Alum (eFood)
ABSTRACT Pomegranate (Punica granatum L.) is a nutritionally dense fruit containing antioxidants and bioactive compounds, demonstrating significant potential in preventing and managing cardiovascular diseases (CVDs). This review evaluates the vasculoprotective effects of various pomegranate components, including the fruit arils, seeds, peel, and flower extracts. The arils and seeds are abundant in anthocyanins, ellagic acid, and polyphenols, while the peel and flower extracts contain high concentrations of punicalagin, gallic acid, and other potent polyphenols. Human and animal studies have consistently demonstrated that pomegranate consumption can lower blood pressure, improve lipid profiles, and reduce inflammation. Researchers found that daily consumption of should be 50–240 mL of pomegranate juice, 1–1.5 g of peel extract, or 200–500 mg of standardized flower extract. However, due to the high natural sugar content of pomegranate juice and its potential to interact with certain medications, moderate consumption is advised. Overall, pomegranate represents a promising nonpharmacological adjunct in CVD prevention. Further research is needed to optimize its use for maximum cardiovascular benefits. This review highlights pomegranate's potential as a valuable, nonpharmaceutical resource for supporting cardiovascular health.